Pandemics ebook - Green, Robert (21st Century Skills Library: Global Perspectives., 2008)
What is a pandemic? What diseases are likely to cause a pandemic? How can the spread of a disease be stopped? Find out about how a disease reaches pandemic proportions and start thinking about what people can do to stop the spread of deadly diseases.